Peningkatan Kompetensi Instruktur Balai Latihan Kerja Kabupaten Karawang dalam Bidang Perawatan dan Perbaikan Lemari Pendingin Showcase: Increasing the Competence of Instructors at Karawang Regency Vocational Training Center in the Maintenance and Repair of Showcase Refrigerator - Wellid, Ismail; Falahuddin, Muhammad Anda; Arman, Muhammad; Surjanto, Ary; Sumeru, Kasni; Nuriyadi, Muhammad; Setyawan, Andriyanto (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
A showcase is a type of refrigerator widely found in small shops and supermarkets, and it maintains the freshness of vegetables, fruits, meat, and drinks. Because showcases are widely used, the potential for working as a technician or entrepreneur in showcase service is promising. This training aims to improve the competence of instructors at BLK Karawang in showcase maintenance and repair. Increased instructor competence impacts the quality of job seekers educated at BLK. The training was carried out in 3 working days, divided into two sessions: theory and practical. The practical material taught participants the proper refrigerant charging, troubleshooting, and repairs on showcases that experienced problems. After the training, the instructors will be evaluated on their ability to deliver the materials to job seekers under the supervision of lecturers from the Department of Refrigeration and Air Conditioning Engineering, Politeknik Negeri Bandung. Based on the evaluation, the instructors have correctly and adequately provided training materials on showcase maintenance and repair to job seekers.